Effect of walnut consumption on neuropsychological development in healthy adolescents: a multi-school randomised controlled trialResearch in context - Ariadna Pinar-Martí; Florence Gignac; Silvia Fernández-Barrés; Dora Romaguera; Aleix Sala-Vila; Iolanda Lázaro; Otavio T. Ranzani; Cecilia Persavento; Anna Delgado; Albert Carol; Jaume Torrent; Judith Gonzalez; et al. (EClinicalMedicine, 2023)
Summary: Background: Omega-3 fatty acids are critical for neuropsychological functioning. Adolescence is increasingly believed to entail brain vulnerability to dietary intake. The potential benefit on adolescent neurodevelopment of consuming walnuts, a source of omega-3 alpha-linolenic acid (ALA), remains unclear. Methods: We conducted a 6-month multi-school-based randomised controlled nutrition intervention trial to assess whether walnut consumption has beneficial effects on the neuropsychological and behavioural development of adolescents. The study took place between 04/01/2016 and 06/30/2017 in twelve different high schools in Barcelona, Spain (ClinicalTrials.gov Identifier: NCT02590848). A total of 771 healthy teenagers aged 11–16 years were randomised into two equal groups (intervention or control). The intervention group received 30 g/day of raw walnut kernels to be incorporated into their diet for 6 months. Multiple primary endpoints concerning neuropsychological (working memory, attention, fluid intelligence, and executive function) and behavioural (socio-emotional and attention deficit hyperactivity disorder [ADHD] symptoms) development were assessed at baseline and after intervention. Red blood cell (RBC) ALA status was determined at baseline and 6 months as a measure of compliance. Main analyses were based on intention-to-treat using a linear mixed-effects model. A per-protocol effect of the intervention was analysed using inverse-probability weighting to account for post-randomisation prognostic factors (including adherence) using generalised estimating equations. Findings: In intention-to-treat analyses, at 6 months there were no statistically significant changes between the intervention and control groups for all primary endpoints. RBC ALA (%) significantly increased only in the intervention group, coefficient = 0.04 (95% Confidence Interval (CI) = 0.03, 0.06; p < 0.0001). The per-protocol (adherence-adjusted) effect on improvement in attention score (hit reaction time variability) was −11.26 ms (95% CI = −19.92, −2.60; p = 0.011) for the intervention group as compared to the control group, improvement in fluid intelligence score was 1.78 (95% CI = 0.90, 2.67; p < 0.0001), and reduction of ADHD symptom score was −2.18 (95% CI = −3.70, −0.67; p = 0.0050). Interpretation: Our study suggested that being prescribed eating walnuts for 6 months did not improve the neuropsychological function of healthy adolescents. However, improved sustained attention, fluid intelligence, and ADHD symptoms were observed in participants who better complied with the walnut intervention. This study provides a foundation for further clinical and epidemiological research on the effect of walnuts and ALA on neurodevelopment in adolescents. Funding: This study was supported by Instituto de Salud Carlos III through the projects ‘CP14/00108, PI16/00261, PI21/00266’ (co-funded by European Union Regional Development Fund ‘A way to make Europe’). The California Walnut Commission (CWC) has given support by supplying the walnuts for free for the Walnuts Smart Snack Dietary Intervention Trial.